Differential Gain Comparison of Optical Planar Amplifier on Silica Glasses Doped with Bi-Ge and Er, Yb Ions (Journal of Material Science and Technology Research, 2020)
The paper presents the measurement and calculation of the optical amplifier gain and the optimal length of the active optical amplifier waveguide doped with Bi-Ge radiation complexes compared to an optical amplifier with active doping with ions Er3+, Yb3+. At present are using optical amplifiers for the high-capacity optical communication systems in the narrow spectral region of 1530–1560 nm, determined by the gain bandwidth of erbium-doped fiber amplifiers (EDFA) or erbium-doped optical planar amplifiers (EDPA) realized as active planar waveguides in the optical integrated circuits technique. However, it is possible increase wavelength region up to 1610 nm, where optical losses of telecommunication fibers are less than 0.3 dB per km, if appropriate amplifiers are available. In this regard, the development of novel optical amplifiers operating in this spectral region have of great importance. The paper summarizes the results measurement of the attenuation and emission spectra for net gain spectra calculation of the new ion exchange Ag+ – Na+ optical Er3+ and Yb3+ doped active planar waveguides realized on silica glass substrates and parameters of novel optical amplifiers for extension of the bandwidth from 1530 to 1610 nm doped by bismuth – erbium ions.